Meningkatkan Daya Kreatif Siswa Menggunakan Teknologi Digital Sebagai Media Pembelajaran Daring - Endang Kumala Ratih; Setyo Yanuartuti (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2021)
Corona virus affects all aspects of life. The teaching and learning process in the world of education is also affected by the corona virus. Changes in learning from conventional to online make teachers, guardians, and students must be able to adapt to the online learning system. To be able to carry out online learning properly, good cooperation between teachers and guardians is needed so that students are able to work on and absorb school material. the only learning media that can be used in mass for the sake of namely by utilizing technology. There are many mass media that can be used to support the teaching and learning process online, but the most important thing here is that it can be connected to the internet network. Especially in the field of art education, it requires applications that can still increase student creativity amid this pandemic. So that in this study the author aims to convey the management of online learning by using several applications that can be used to support student creativity. This study uses a management approach to analyze data and controls in the implementation of online learning. This research uses descriptive qualitative method, data collection uses participatory observation methods, interviews, literature study, and documentation. Through this research, it can be seen that by using the proper management and utilization of media online learning for art education will continue and can hone children's creativity.